Odpowiedzi

2009-11-04T19:33:10+01:00
A) 10x2 - 15xy - 9x2 - 6xy + 4y2 = x2 - 9xy + 4y2
b) 25x2 - 16y2 - 1/4(100x2 - 20xy + 4y2) = 25x2 - 16y2 - 25x2 + 5xy - 1y2 = -17y2 + 5xy
c) 2 - a + 18 + 6√2a + 4a2 = 20 - a - 6√2a + 4a2
d) y - √7y + 7 - 4x2 - 49y2
e) -x2y4 - 9x2 - 9x2 = -x2y4 - 18x2
3 2 3
2009-11-04T19:42:56+01:00
A) 5x(2x-3y)-(3x-2y)² = 10x2 - 15xy - 9x2 + 12xy - 4y2 = 19 x2 - 3xy - 4y2

b) (5x-4y)(5x+4y)-¼(10x-2y)²= 25x2 - 16y2 -1/4 ( 100x2 - 40xy + 4y2) =
25x2 - 16y2 - 25x2 + 10xy +y2= -15y2 + 10xy

c) (√2+a)(a-√2)+(-3√2+2a)² = a2 - 2 - 36 -12√2 + 4a2 = 5a2 - 38 -12√2

d) (-y-√7)² -(2x²-7y)(7y-2x²) = -y2 + 2√7y +7 -14x2y + 4x4 + 49y2 - 14 x2y =
48x2 + 2√7y +7 + 4x4 - 28 x2y

e) (xy²+3x)(-xy²+3x)-(3x)²= 9x2 - x2y4 - 9x2 = -x2y4
3 2 3
2009-11-04T20:07:13+01:00
A)=10x²-15xy-(9x²-12xy+4y²)=10x²-15xy-9x²+12xy-4y²=x²-4y²-3xy
b)=25x²-16y²-1/4*(100x²-40xy+4y²)=25x²-16y²-25x²+10xy-y²=-17y²+10xy
c)=(a√2-2+a²-a√2)+(18+4a²-12√2a)=-2+a²+18+4a²-12√2a=5a²+16-12√2a
d)=y²+7-2√7y-(14x²y-4x⁴-49y²+14x²y)=y²+7-2√7y-14x²y+4x⁴+49y²-14x²y=50y²-28x²y+4x⁴+7-2√7y
e)=-x²y⁴+3x²y²-3x²y²+9x²-9x²=-x²y⁴
4 5 4